REALIZATION OF IDEAS N. I. VAVILOV'S IDEAS IN THE BARLEY BREEDING IN SIBERIA - N. A. Surin; N. E. Lyakhova; S. A. Gerasimov; A. G. Lipshin (Труды по прикладной ботанике, генетике и селекции)
In his publications, N. I. Vavilov used to emphasize the need to use local source material in cereal crop breeding, marking out the value of East Siberian varieties with their long evolutionary background in extreme climate environments. This idea of N. I. Vavilov was proven by the development of barley cultivars in Siberia. In the northern subtaiga and taiga regions of Siberia, six-row barley cultivars are preferred. Crosses between the cultivar ‘Chervonets’ and barley varieties developed in North America resulted in releasing 10 cultivars. In the forest-steppe zone, preference is given to two-row barleys. ‘Viner’ and ‘Omsky 13709’ cultivars participated in the development of 21 new barley cultivars. A breeding program has been worked out and launched to release varieties resistant to a complex of extreme environments.